The results form in the Hawaii Ironman - Janusz Mikołajczyk; Monika Prątnicka; Krzysztof Byzdra; Mirosław Piatek; Robert Stępniak (Kazimierz Wielki University, 2017)
The study made it possible to assess the progress of the results, which the best players obtained at the turn of the years 1978-2014. The difference between the time of the first launch in 1978 and the best obtained in 2011 is 03:43:02. It should be mentioned that in 1981 there has been a change in routes of Kailua-Kona and to this day, the games are exactly on the same route. The difference between the time of the 1981 and the difference between the best is 01:35:41. The research show that the biggest impact on the final result is time on the cycling route, this is due to the rapid development of the bicycle equipment, which allowed players to improve the time of 06:58:00 from 1978 to 04:18:23-2006 r.